Gambaran Latihan Fisik pada Pasien Diabetes Mellitus Tipe 2 di Masa Pandemi COVID-19 - Aisyah Istiqomah; Dadang Purnama; Nursiswati Nursiswati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to identify physical exercise features in patients with type 2 diabetes mellitus during the COVID-19 pandemic. The research method used is a narrative review by searching articles using Pubmed, Cinahl, and Sage Journals. The results of the study showed that eight pieces reported that there was a decrease in the frequency and intensity of physical exercise in patients with type 2 diabetes during the COVID-19 pandemic, and two articles reported that respondents continued to do physical activity during the COVID-19 pandemic. In conclusion, the frequency of physical activity carried out by people with diabetes during the COVID-19 pandemic has decreased and remained the same. Still, most of them are described as experiencing a decrease in exercise intensity and frequency. Keywords: Type 2 Diabetes Mellitus, Physical Exercise, COVID-19 Pandemic